Adapting to Teaching and Learning in Open-Plan Schools
IX, 232 p.
Keywords: In recent years many countries have built or renovated schools incorporating open plan design. These new spaces are advocated on the basis of claims that they promote fresh, productive ways to teach and learn that address the needs of students in this century, resulting in improved academic and well-being outcomes. These new approaches include teachers planning and teaching in teams, grouping students more flexibly, developing more coherent and comprehensive curricula, personalising student learning experiences, and providing closer teacher-student relationships. In this book we report on a three-year study of six low SES Years 7–10 secondary schools in regional Victoria, Australia, where staff and students adapted to these new settings. In researching this transitional phase, we focused on the practical reasoning of school leaders, teachers and students in adapting organisational, pedagogical, and curricular structures to enable sustainable new learning environments. We report on approaches across the different schools to structural organisation of students in year-level groupings, distributed leadership, teacher and pre-service teacher professional learning, student advocacy and wellbeing, use of techno-mediated learning, personalising student learning experiences, and curriculum design and enactment. We found that these new settings posed significant challenges for teachers and students and that successful adaptation depended on many interconnected factors. We draw out the implications for successful adaptation in other like settings.